Lessons from establishing a football-specific registry of anterior cruciate ligament injuries - data collection and first epidemiological data. Issue 4 (2nd October 2022) - Szymski, Dominik; Koch, Matthias; Zeman, Florian; Zellner, Johannes; Achenbach, Leonard; Bloch, Hendrik; Pfeifer, Christian; Alt, Volker; Krutsch, Werner
ABSTRACT: Purpose: Anterior cruciate ligament (ACL) injuries are a common severe type of football injury. Injury prevention measures should be adapted to the respective type of sports and be based on sports-specific strategies. A football-specific ACL registry including prospective ACL injury data of both sexes and at different skill levels is lacking in the literature. Methods: In Germany, a prospective 'ACL registry for German Football' was implemented in the 2014–15 football season. Professional football leagues (1 st to 3 rd national league), semi-professional football leagues (4 th until 6 th leagues) and amateur football leagues (7 th league and below) were monitored regarding the incidence of ACL injuries, risk factors, general treatment and rehabilitation. After the registration of an injury, injured players were sent a standardised questionnaire. Results: Overall, 1, 206 ACL ruptures were registered in the investigated population of more than 56, 000 players, resulting in a prevalence of 2.1%. The highest prevalence was found in men's amateur football (2.7%) as well as in men's and women's professional football (2.1% each). Conclusion: This football-specific ACL registry provides for the first-time longitudinal data about ACL injury patterns and treatment at all football levels. This report describes the considerations for data collection and presents first epidemiological results of 6 years of ACL injury registration.